2014
DOI: 10.1002/jeab.94
|View full text |Cite
|
Sign up to set email alerts
|

Generalized conditioned reinforcement with pigeons in a token economy

Abstract: Six pigeons were studied in a token economy in which tokens could be produced and exchanged for food on one side of an experimental chamber and for water on the opposite side of the chamber. Responses on one key produced tokens according to a token-production fixed ratio (FR) schedule. Responses on a second key produced an exchange period during which tokens were exchanged for water or food. In Experiment 1a, food tokens could be earned and exchanged under restricted food budgets, and water tokens could be ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 23 publications
3
21
0
Order By: Relevance
“…The selective substitution that occurred under price‐change conditions is consistent with prior results (DeFulio et al, ; Tan & Hackenberg, ), and underscores an important function of generalized reinforcers—that of standing in place of other reinforcers. Indeed, such selective substitution, in which generalized reinforcers are earned and exchanged for multiple reinforcers, may be a distinctive function of generalized reinforcers, and key to their reinforcing efficacy.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The selective substitution that occurred under price‐change conditions is consistent with prior results (DeFulio et al, ; Tan & Hackenberg, ), and underscores an important function of generalized reinforcers—that of standing in place of other reinforcers. Indeed, such selective substitution, in which generalized reinforcers are earned and exchanged for multiple reinforcers, may be a distinctive function of generalized reinforcers, and key to their reinforcing efficacy.…”
Section: Discussionsupporting
confidence: 86%
“…The present procedures were not designed to distinguish the reinforcing from the discriminative functions of the embedded correlated stimuli; it is likely that both contributed to the results, especially given these pigeons’ extensive histories with generalized token reinforcement—histories that predated the present study. These pigeons served previously in the DeFulio et al () study, along with two additional subjects not part of the present investigation. In that study, five of six pigeons showed consistent preference for the generalized tokens over equally‐priced specific tokens, including the three pigeons (999, 271, 113) that preferred the generalized tokens in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are broadly consistent with laboratory research with pigeons in token economies (DeFulio, Yankelevitz, Bullock, & Hackenberg, ). Under various experimental arrangements, pigeons could produce either specific tokens or generalized tokens.…”
Section: Functional Taxonomy Of Token Systemssupporting
confidence: 54%
“…The present study was designed to explore in greater depth these types of reinforcer interactions in a generalized token economy. First, unlike the DeFulio et al () study, some conditions in the present study were conducted in a fully closed economy in which daily intake of food and water occurred within the experimental sessions, designed to enhance the generalized functions of the tokens. Second, using known complementary reinforcers (food and water) but including a generalized type with the potential to function as a substitute for these more specific reinforcers, we directly assessed the substitutability function of the generalized tokens.…”
mentioning
confidence: 99%